Drug Utilization Studies in Pregnant Women for Newly Licensed Medicinal Products: A Contribution from IMI ConcePTION - Sandra Lopez-Leon; Anja Geldhof; Julie Scotto; Keele Wurst; Meritxell Sabidó; Jingping Mo; Ditte Molgaard-Nielsen; Jorieke E. H. Bergman; Xuan Anh Phi; Sue Jordan (Hindawi Limited, 2024)
Purpose. Studies focusing on safety outcomes typically require large populations to comprehensively characterise the patient groups exposed to the medicines under investigation. However, there is often less information for subpopulations, such as pregnant or breastfeeding women, particularly when new medicines are considered. It is important to understand what information can be obtained from drug utilization studies (DUS) involving pregnant women in the early years postmarketing to provide supportive information for safety studies. The aims of this literature review are to (1) identify and review DUS for new medicines in pregnancy and breastfeeding and (2) list and summarise key information items to be reported in a DUS for new medicines in pregnancy. Methods. To identify postmarketing DUS of new prescription medicines or enantiomers in pregnancy, a systematic literature review was undertaken in PubMed and Embase between January 2015 and June 2022. In addition, the complete database of the ENCePP EU PAS Register was systematically searched to June 2022. Results. We identified 11 published DUS on new medicines in pregnancy from the ENCePP EU PAS Register and none from other sources. No studies on breastfeeding were identified. The 11 identified publications reported the medicine's use for the first 3 to 5 years after marketing approval. No reports assessed utilization in the first 3 years of approval. It was usual to issue interim reports annually (7 studies). All studies concerned conditions managed in ambulatory care (primary care and outpatient facilities) and included some primary care prescribing. Most (n=8) only had prescribing/dispensing data available at individual level for ambulatory care; outpatient prescribing was included in three of these studies Three studies held a limited amount of in-hospital prescribing data. A DUS can confirm at an early stage whether there are sufficient exposed pregnancies in available data sources to ensure a safety study is powered to detect a difference in the prevalence of adverse pregnancy or infant outcomes or if additional data from other databases are needed. A DUS may also help address methodological considerations such as selection of comparators. DUS can be performed embedded in a DUS in the general population, in a cohort of women of childbearing age, or in a cohort of pregnant women. Conclusion. This review summarises key aspects of a DUS for new medicines in pregnancy. DUS for new medicines in pregnancy should be planned before marketing, scheduled for the first 3 to 5 years after release, with annual interim/progress reports, and reported in peer-reviewed journals. By offering detailed information on data sources, exposure timing, prevalence and location, coprescribing, comorbidities, coexposures, and demographics, a DUS will offer a firm foundation for safety studies and will help to contextualize spontaneous reporting of serious adverse events.